Автомобильчик Тум: [повесть-сказка] / О. Сербина ; [худ. В. Коробейников] - Сербина Олеся (Очень прикольная книга, 2011)
1 - 3 кл. Экземпляры: (20220201) / Инвентарный номер: 3981 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С32 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6